RANCANGAN & SIMULASI MICRO PUNCH UNTUK PEMBUATAN PELAT PENYAMBUNG TULANG RAHANG (MINI PLATE) - Muhamad Hilal Khoidar; Yusuf Bahtiar Pradana; Muhammad Haritsah Amrullah; Sugianto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Bone joint plates have a high production potential. This can be seen from the number of cases related to trauma to the bone which has increased quite high in Indonesia. The jaw bone joint plate or commonly known as the mini plate serves to connect the bones in the jaw that has been traumatized or broken. The manufacture of mini plates generally uses an EDM machine, wire cutting and laser cutting which can only process with a gradual working principle. Based on the description above, it is necessary to manufacture a micro punch machine for the manufacture of jaw bone joint plates (mini plates), so that they can be used to mass produce mini plates. This study aims to design a mini punch machine for the manufacture of a mini plate using a research method that refers to the book Product Design and Development (Karl T. Ulrich, Steven D. Eppinger) in order to obtain an optimal machine design. The results obtained based on the research method used, obtained a micro punch machine design for the manufacture of a mini plate using the working principle of a progressive tool, a pneumatic prime mover and a material strip drive using a fedder system.